Blood oxidative stress biomarkers in women: influence of oral contraception, exercise, and N-acetylcysteine - Quinn, K. M.; Roberts, L.; Cox, A. J.; Borg, D. N.; Pennell, E. N.; McKeating, D. R.; Fisher, J. J.; Perkins, A. V.; Minahan, C. (European Journal of Applied Physiology, 2022)
Purpose To compare physiological responses to submaximal cycling and sprint cycling performance in women using oral contraceptives (WomenOC) and naturally cycling women (WomenNC) and to determine whether N-acetylcysteine (NAC) supplementation mediates these responses.